Avian anaesthesia and analgesia - McMunn , Kimberly A (Wildlife Rehabilitation Bulletin, 2022)
<span style="color: #000000; font-family: -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen, Ubuntu, Cantarell, 'Fira Sans', 'Droid Sans', 'Helvetica Neue', sans-serif; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Wildlife rehabilitators are often presented with injured birds. We recognize that birds are not dogs and cats and, therefore, require specialized protocols for anaesthesia and analgesia. This paper discusses recent research on anaesthesia and analgesia in birds, with a focus on a multimodal approach to treatment. Rehabilitators will need to work closely with veterinarians to provide the best care for wild bird patients.